Genetic and environmental factors associated with alteration of filtration slit proteins and their functions: a scoping review - Adepoju, Aolat Adepeju; Muhammad, Mubarak Abubakar; Adamson, Mubashir Mayowa; Adewale, Shakirudeen Abdulqodri; Adekunle, Adedeji Tayyib; Ojulari, Lekan Sheriff; Alagbonsi, Abdullateef Isiaka (Frontiers in Nephrology, 2025)
BackgroundFiltration slit proteins are important for maintaining the integrity of the glomerular filtration barrier. Genetic mutations and environmental factors can disrupt their structure and functions, leading to proteinuria and kidney diseases. This scoping review aims to synthesize the available information on the genetic and environmental factors that affect the slit proteins to enhance our understanding of the (patho)physiology of glomerular filtration.MethodsOnline databases such as Wiley and PubMed were used. Relevant studies were selected focusing on genetic variations, environmental influences, and their impact on filtration slit proteins. Data extraction and synthesis were conducted to highlight key themes and knowledge gaps.ResultsWe summarized at least 20 proteins and their genes, including nephrin, podocin, phospholipase C Epsilon 1 (PLCE1), CD2-Associated Protein (CD2AP), ITGA 3, synaptopodin, myosin 1E (MYO1E), flotillin-2 (Flot2), podocalyxin, FAT1, Apo Hemoglobin-Haptoglobin (Apo Hb-Hp), spermidine, P-Cadherin, ephrin B1, Zo- 1 (Zona Occluden), MAGI 1&2 (MAGUK inverted), Par- complex, IP-10 (interferon-inducible protein), neurexin 1, and liver type fatty acid binding protein. We also reported at least 8 environmental factors, including oxidative stress, inflammation, heavy metals, air-bone pollutants, high-fat diets, vitamins and micronutrient deficiency, mechanical stretch, and nephrotoxic agents.ConclusionThis review highlights various filtration slit proteins and the mechanisms of their alterations by genetic and environmental factors. It contributes to efforts toward personalized therapeutic strategies for disorders of glomerular filtration.